In-Silico Test of Myricetin, Phyllanthin, Luteolin Compounds Against SARS-CoV-2 Proteins - Noviyanti, Vidia; Arifin, Nuha Haifa; Ikfini, Hayu; Febriansah, Rifki (Pharmaceutical Sciences and Research, 2025)
Coronavirus disease 2019 (COVID-19), which emerged in late 2019 and was first detected in Indonesia in March 2020, has significantly reshaped the country’s public health landscape. Aside from the viral outbreak itself, a decline in immunity among the population due to excessive concern about the pandemic has also become a significant issue. This study aimed to evaluate the potential of myricetin, phyllanthin, and luteolin compounds as inhibitors of the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) virus by targeting the main protease and spike glycoprotein receptor-binding domain proteins through in silico molecular docking. Remdesivir and favipiravir were used as comparison compounds. The molecular docking process involved several stages including structural preparation, protein preparation, method validation, and docking between the compounds with the target protein. The docking results were assessed based on binding energy values, where lower energy indicates a stronger and more stable interaction between the compound and the protein. The binding energies of myricetin, phyllanthin, luteolin, favipiravir and remdesivir compounds with the main protease protein were -6.2, -5.5, -5.3, -4,4, and -5.5 kcal/mol, respectively. The binding energies of those compounds with spike glycoprotein-RBD were -6.0, -4.2, -4.8, -6.0, and -5.3 kcal/mol, respectively. The results showed that myricetin exhibited stronger binding affinity compared to phyllanthin and luteolin and may serve as a promising inhibitor of main protease and spike glycoprotein receptor-binding domain proteins.